2017
DOI: 10.1016/j.xphs.2017.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liver Disease on Hepatic Transporter Expression and Function

Abstract: Liver disease can alter the disposition of xenobiotics and endogenous substances. Regulatory agencies such as the Food and Drug Administration (FDA) and the European Medicines Evaluation Agency (EMEA) recommend, if possible, studying the effect of liver disease on drugs under development to guide specific dose recommendations in these patients. While extensive research has been conducted to characterize the effect of liver disease on drug-metabolizing enzymes, emerging data have implicated that the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 202 publications
(220 reference statements)
3
68
1
Order By: Relevance
“…Although simeprevir exposure was increased by 1.7‐fold when administered in combination with odalasvir, compared with simeprevir administered alone in a healthy volunteer drug–drug interaction study, results from cohort 1 indicated that there is no significant interaction in HCV‐infected patients. The difference in interaction effect may be related to the effect of liver disease on hepatic transporters . In the phase IIb PILLAR study of simeprevir in combination with pegIFN and ribavirin, simeprevir doses of 75 and 150 mg QD were evaluated in treatment‐naïve, HCV‐infected patients, and no significant difference in SVR rates was observed, only a trend for higher SVR with the higher dose in some difficult‐to‐cure subpopulations .…”
Section: Discussionmentioning
confidence: 99%
“…Although simeprevir exposure was increased by 1.7‐fold when administered in combination with odalasvir, compared with simeprevir administered alone in a healthy volunteer drug–drug interaction study, results from cohort 1 indicated that there is no significant interaction in HCV‐infected patients. The difference in interaction effect may be related to the effect of liver disease on hepatic transporters . In the phase IIb PILLAR study of simeprevir in combination with pegIFN and ribavirin, simeprevir doses of 75 and 150 mg QD were evaluated in treatment‐naïve, HCV‐infected patients, and no significant difference in SVR rates was observed, only a trend for higher SVR with the higher dose in some difficult‐to‐cure subpopulations .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the DDI on viral‐load reduction can only be evaluated when this DAA combination is evaluated in patients. In addition, differences in metabolism and transporter expression between healthy volunteers and HCV‐infected patients may limit extrapolation of results . Another limitation is that the effect of simeprevir on the pharmacokinetics of odalasvir was estimated without taking into account odalasvir accumulation over time; therefore, the data presented assume steady‐state of odalasvir.…”
Section: Discussionmentioning
confidence: 99%
“…grade 3) and aspartate aminotransferase (peak 3. and transporter expression between healthy volunteers and HCVinfected patients may limit extrapolation of results. 21 Another limitation is that the effect of simeprevir on the pharmacokinetics of odalasvir was estimated without taking into account odalasvir accumulation over time; therefore, the data presented assume steadystate of odalasvir. This can be corrected for by comparing data between Groups 1 and 2 after 7 days of treatment with odalasvir.…”
Section: Safetymentioning
confidence: 99%
“…In addition to investigating PK in healthy volunteers, there should be close attention to understanding the compound’s PK characteristics in hepatically impaired populations. Several pathophysiological changes, which regularly occur in individuals with cirrhosis and PH, can significantly impact drug disposition in this population (Table ) . The 2003 U.S. Food and Drug Administration (FDA) Guidance for Industry recommends a formal PK study in hepatically impaired individuals if (1) hepatic metabolism and/or excretion accounts for >20% of the absorbed drug’s or its active metabolite’s disposition, or (2) the test compound is either known or suspected to have a narrow therapeutic window, or (3) there is insufficient information about the compound’s metabolism and excretion and its predicted therapeutic window.…”
Section: Pharmacokinetic and Pharmacodynamic Evaluation In Ph Clinicamentioning
confidence: 99%
“…Several pathophysiological changes, which regularly occur in individuals with cirrhosis and PH, can significantly impact drug disposition in this population ( Table 2). (18)(19)(20)(21)(22)(23) The 2003 U.S. Food and Drug Administration (FDA) Guidance for Industry (24) recommends a formal PK study in hepatically impaired individuals if (1) hepatic metabolism and/or excretion accounts for >20% of the absorbed drug's or its active metabolite's disposition, or (2) the test compound is either known or suspected to have a narrow therapeutic window, or (3) there is insufficient information about the compound's metabolism and excretion and its predicted therapeutic window. However, a formal PK study in hepatically impaired individuals may not be necessary if a compound is entirely renally excreted with no involvement of the liver, or if a drug is gaseous or volatile and its active metabolite(s) are primarily eliminated by the lungs.…”
Section: Pharmacokinetic and Pharmacodynamic Evaluation In Ph Clinicamentioning
confidence: 99%